Missions to Mars : a new era of rover and spacecraft discovery on the Red Planet - Crumpler, Larry S. (Larry Steven) (Harper Design, an Imprint of HarperCollins Publishers, 2021)
"From a long-term planning lead for the Mars Exploration Rover Project comes this vivid insider account of some of NASA's most vital and exciting missions to the Red Planet, illustrated with full-color photographs-a wondrous chronicle of unprecedented scientific discovery and the search for evidence of life on Mars"--